2002
DOI: 10.1177/1054773802011002003
|View full text |Cite
|
Sign up to set email alerts
|

Nonfatal Injury Experiences Among Women on Family Farms

Abstract: Agricultural injury occurrence was determined among 1,096 working farm women in Texas and Louisiana. The 1-year cumulative incidence was 4.8%. Lower extremities were the body parts most frequently injured. The leading external causes were contact with foreign object, followed by falls and overdoing/ lifting. The seasonal pattern of injury was consistent with warm weather. The factors predictive of increased injury risk in multiple logistic regression included large animal farm type, greater time commitment, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One obvious factor related to the incidence of acute injuries is the amount of time spent working on farms. Researchers have reported an approximately 3% increase in injury rate for every hour worked (Kidd et al, 1996;Stueland et al, 1997;Carruth et al, 2002). Many of these acute injuries are major traumas to the body, including fractures, lacerations, and internal bleeding.…”
Section: Acute Injuriesmentioning
confidence: 98%
See 1 more Smart Citation
“…One obvious factor related to the incidence of acute injuries is the amount of time spent working on farms. Researchers have reported an approximately 3% increase in injury rate for every hour worked (Kidd et al, 1996;Stueland et al, 1997;Carruth et al, 2002). Many of these acute injuries are major traumas to the body, including fractures, lacerations, and internal bleeding.…”
Section: Acute Injuriesmentioning
confidence: 98%
“…Hwang et al (2001) reported that more than 90% of farmers in the state of New York reported having a severe injury in the previous year. A breakdown of injuries showed rates for contusions were between 11% and 52%, and those for lacerations were between 12.5% and 34.0% (Swanson et al, 1987;Schulman et al, 1997;Stueland et al, 1997;Gerberich et al, 2001;Carruth et al, 2002;Munshi et al, 2002;Browning et al, 2003). The magnitude of the prevalence of injuries appears to depend upon the agricultural subsector (Table 26.1) with some of the highest rates for beef, hog, and sheep farmers, followed by cash grain, nursery, field crop, dairy, and poultry farmers, and (considered as a group) vegetable, fruit, and nut farmers .…”
Section: Acute Injuriesmentioning
confidence: 99%
“…Back pain has been identified as a reason farmers restrict farm activities, and is a predictor of increased risk for non-fatal farm-related injuries among farm women (Carruth, Skarke, Moffett, & Prestholdt, 2002;CDC, 1999). The purpose of this study was to determine the incidence of back pain; examine the relationships between back pain and psychosocial factors, chronic illness, and selected farm work-related activities; and identify predictors of back pain from an existing data set of farm women in southeastern Louisiana.…”
Section: Self-reported Back Pain Among Farm Women In Southeast Louisianamentioning
confidence: 99%